A Comparative Approach to Assessing Assessment. Revising the Scoring Chart for the Authorized Translator’s Examination in Finland - Salmi Leena; Kivilehto Marja (Routledge, 2022)
The error-based scoring chart of the Finnish Authorized Translators’ Examination was recently revised drawing on an analysis of how it had been applied in previous examinations and on feedback from the assessors. The previous scoring chart had two error categories, errors of equivalence and errors of acceptability/readability, comprising 14 error types on the whole. The revised scoring chart has an additional third category of errors related to the task accomplishment, with special reference to translating official documents. It has also fewer error types: seven instead of 14. The new scoring chart was introduced in 2017. This chapter discusses how the revision process was conducted and analyzes how the new error types were applied in the examinations during 2017–2018, in comparison to a similar analysis with earlier data. The data consist of 112 English-Finnish and Finnish-English translations assessed in the examinations of 2012–2014, and 112 translations between the same languages from the examinations of 2017 and 2018 (56 from each year). The chapter also discusses ideas for further improving the Finnish system along the lines of the criterion-referenced assessment system developed by the Australian National Accreditation Authority for Translators and Interpreters (NAATI).
Institutional Translation and Interpreting. Assessing Practices and Managing for Quality